The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1051/rnd:2006015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary protein on the amino acid supply and threonine metabolism in the pregnant rat

Abstract: -To characterise the effects of dietary protein content on threonine metabolism during pregnancy, rats were fed diets containing 18% or 9% protein and then killed at different stages of gestation. Serum threonine concentrations fell significantly faster in the animals fed the diet containing 9% protein when compared to those fed the diet containing 18% protein. On day 4 of gestation the rate of threonine oxidation was higher in maternal liver homogenates prepared from the animals fed the diet containing 18% pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Maternal protein restriction (60 g protein/kg diet) throughout pregnancy in rats decreased maternal serum concentration of the branched chain amino acids (valine, isoleucine and leucine) by 29-36%, and the threonine concentration was reduced by 80% compared with the control group fed on 180 g protein/kg diet (Rees et al 1999). Similar results have been reported in rats showing significantly decreased maternal serum concentrations of the branched-chain amino acids and/or the total essential amino acids under maternal protein restriction (Bhasin et al 2009;Parimi et al 2004;Rees et al 2006). BeWo cells have been used to study the effects of amino acid restriction on amino acid transport (Jones et al 2006), in which DMEM Glutamax 1 was used as control, while the amino acid deprivation medium was a balanced salt solution containing no nonessential, and 50% essential amino acids used in MEM.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Maternal protein restriction (60 g protein/kg diet) throughout pregnancy in rats decreased maternal serum concentration of the branched chain amino acids (valine, isoleucine and leucine) by 29-36%, and the threonine concentration was reduced by 80% compared with the control group fed on 180 g protein/kg diet (Rees et al 1999). Similar results have been reported in rats showing significantly decreased maternal serum concentrations of the branched-chain amino acids and/or the total essential amino acids under maternal protein restriction (Bhasin et al 2009;Parimi et al 2004;Rees et al 2006). BeWo cells have been used to study the effects of amino acid restriction on amino acid transport (Jones et al 2006), in which DMEM Glutamax 1 was used as control, while the amino acid deprivation medium was a balanced salt solution containing no nonessential, and 50% essential amino acids used in MEM.…”
Section: Discussionsupporting
confidence: 76%
“…It has been shown that maternal low protein diet or the maternal nutrient restriction causes significant decrease in free amino acid concentrations in maternal circulation (Bhasin et al 2009;Kilberg et al 2009;Kwon et al 2004;Rees et al 2006). Branched-chain amino acids (BCAAs), particularly leucine, stimulate leptin production by rat adipocytes in vivo (Lynch et al 2006) and in vitro (Roh et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase in the essential AA threonine with advancing gestation was previously reported [ 19 ]. Rees et al [ 26 ] studied threonine metabolism in the pregnant rat and concluded that dietary protein induced increases in serine-threonine dehydratase activity favored conservation of this AA rather than its oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, turnover of methionine in the rat is similar to turnover of other amino acids, such as threonine and serine, the oxidation of which also declines as gestation proceeds (14). These changes may be part of a conservation mechanism that accompanies a mobilization of maternal protein reserves to support the rapid growth of the fetuses during the final stages of gestation.…”
Section: Methionine Metabolism In Maternal Livermentioning
confidence: 94%